Salivary SARS-CoV-2 antibody detection using S1-RBD protein-immobilized 3D melt electrowritten poly(ε-caprolactone) scaffolds. Issue 38 (31st August 2022) - Han, Pingping; Liu, Chun; Staples, Reuben; Moran, Corey S.; Ramachandra, Srinivas Sulugodu; Gómez-Cerezo, Maria Natividad; Ivanovski, Sašo
Abstract : Our work developed a 3D SARS-CoV-2 antibody detection platform in non-invasive saliva samples using S1-RBD protein-immobilized 3D melt electrowritten poly(ε-caprolactone) scaffolds. Abstract : Sensitive detection of immunoglobulin antibodies against SARS-CoV-2 during the COVID-19 pandemic is critical to monitor the adaptive immune response after BNT162b2 mRNA vaccination. Currently employed binding antibody detection tests using 2D microplate-based enzyme-linked immunosorbent assays (ELISA) are limited by the degree of sensitivity. In this study, a 3D antibody test was developed by immobilizing the receptor-binding domain on Spike subunit 1 (S1-RBD) of SARS-CoV-2 onto engineered melt electrowritten (MEW) poly(ε-caprolactone) (PCL) scaffolds (pore: 500 μm, fiber diameter: 17 μm) using carbodiimide crosslinker chemistry. Protein immobilization was confirmed using X-ray photoelectron spectroscopy (XPS) by the presence of peaks corresponding with nitrogen. Self-developed indirect ELISA was performed to assess the functionality of the 3D platform in comparison with a standard 2D tissue culture plate (TCP) system, using whole unstimulated saliva samples from 14 non-vaccinated and 20 vaccinated participants (1- and 3- weeks post-dose 1; 3 days, 1 week and 3 weeks post-dose 2) without prior SARS-CoV-2 infection. The three-dimensional S1-RBD PCL scaffolds, while demonstrating a kinetic trend comparable to 2D TCP, exhibited significantly higher sensitivity and detection levels for all three immunoglobulins assayed (IgG, IgM, and IgA). These novel findings highlight the potential of MEW PCL constructs in the development of improved low-cost, point-of-care, and self-assessing diagnostic platforms for the detection and monitoring of SARS-CoV-2 antibodies.